Characterizing the fluid dynamics in the flow fields of cylindrical orbitally shaken bioreactors with different geometry sizes. Issue 8 (14th May 2018) - Zhu, Likuan; Han, Wang; Song, Boyan; Wang, Zhenlong
Abstract: Orbitally shaken bioreactors (OSRs) are commonly used for the cultivation of mammalian cells in suspension. To aid the geometry designing and optimizing of OSRs, we conducted a three‐dimensional computational fluid dynamics (CFD) simulation to characterize the flow fields in a 10 L cylindrical OSR with different vessel diameters. The liquid wave shape captured by a camera experimentally validated the CFD models established for the cylindrical OSR. The geometry size effect on volumetric mass transfer coefficient ( kL a ) and hydromechanical stress was analyzed by varying the ratio of vessel diameter ( d ) to liquid height at static ( h L ), d/h L. The highest value of kL a about 30 h −1 was observed in the cylindrical vessel with the d/h L of 6.35. Moreover, the magnitudes of shear stress and energy dissipation rate in all the vessels tested were below their minimum values causing cells damage separately, which indicated that the hydromechanical‐stress environment in OSRs is suitable for cells cultivation in suspension. Finally, the CFD results suggested that the d/h L higher than 8.80 should not be adopted for the 10 L cylindrical OSR at the shaking speed of 180 rpm because the "out of phase" state probably will happen there.